Correction: Advances in energy systems for valorization of aqueous byproducts generated from hydrothermal processing of biomass and systems thinking. Issue 21 (21st October 2019) - Gu, Yexuan; Zhang, Xuesong; Deal, Brian; Han, Lujia; Zheng, Jilu; Ben, Haoxi
Abstract : Correction for 'Advances in energy systems for valorization of aqueous byproducts generated from hydrothermal processing of biomass and systems thinking' by Yexuan Gu et al., Green Chem., 2019, 21, 2518–2543.